2022
DOI: 10.1080/02640414.2021.2022275
|View full text |Cite
|
Sign up to set email alerts
|

Angle specific analysis of hamstrings and quadriceps isokinetic torque identify residual deficits in soccer players following ACL reconstruction: a longitudinal investigation

Abstract: Angle specific analysis of hamstrings and quadriceps isokinetic torque identify residual deficits in soccer players following ACL reconstruction: a longitudinal investigation. Journal of Sports Sciences, 40 (8). pp. 871-877.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…4 ) and hip moment arm (Table 1 ) as the hip flexes. Irrespective of hip flexion angle, the maximum knee flexion torque is centered around 30° of knee flexion (Table 5 ) and ranges between 0 and 45° of knee flexion during isometric [ 79 , 127 , 130 , 145 , 149 , 150 , 152 155 , 158 , 198 – 202 ] and 15–70° during isokinetic [ 20 , 24 , 128 , 153 , 158 , 192 , 203 – 221 ] tests.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…4 ) and hip moment arm (Table 1 ) as the hip flexes. Irrespective of hip flexion angle, the maximum knee flexion torque is centered around 30° of knee flexion (Table 5 ) and ranges between 0 and 45° of knee flexion during isometric [ 79 , 127 , 130 , 145 , 149 , 150 , 152 155 , 158 , 198 – 202 ] and 15–70° during isokinetic [ 20 , 24 , 128 , 153 , 158 , 192 , 203 – 221 ] tests.…”
Section: Main Textmentioning
confidence: 99%
“…4) and hip moment arm (Table 1) as the hip flexes. Irrespective of hip flexion angle, the maximum knee flexion torque is centered around 30° of knee flexion (Table 5) and ranges between 0 and 45° of knee flexion during isometric [79, 127, 130, 145, 149, 150, 152-155, 158, 198-202] and 15-70° during isokinetic [20,24,128,153,158,192,[203][204][205][206][207][208][209][210][211][212][213][214][215][216][217][218][219][220][221] tests. Several studies have also shown that the maximum knee flexion torque occurred at more flexed knee angles when the hip was more flexed [127,144,145,206] which makes sense given that this would approximately maintain muscle length; i.e., the muscle length rather than the joint angles themselves appear to dictate muscle strength.…”
Section: Torque-angle Relationshipmentioning
confidence: 99%
“…All data processing was conducted in MATLAB (R2022a; MathWorks, Inc., Natick, MA). Imported joint moment and positional data were initially filtered using a recursive, second-order, low-pass Butterworth filter with cutoff frequency of 10 Hz (29). Joint angular velocities were calculated as the first time derivative of joint angle, and the isokinetic range for all testing conditions was defined when calculated angular velocity was at least 95% of the target velocity (4).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, peak joint moment values for the knee extensors are typically observed between 60°and 70°and peak knee flexor moment values occurring at 25°-40°when this hip is flexed at 85° (8,29). Therefore these discrete ratios provide a single value based on peak joint moments that occur at different joint angles (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation